1, 3, 5‐Tris(4‐bromophenyl)benzene prenucleation clusters from metadynamics. Issue 2 (15th February 2014) - Salvalaglio, Matteo; Giberti, Federico; Parrinello, Michele
<x xml:space="preserve">Abstract</x> Recent experimental evidence has shown that the nucleation of 1, 3, 5‐tris(4‐bromophenyl)benzene (3BrY) follows a two‐step mechanism. In this work, the formation of clusters of 3BrY from homogeneous water and methanol solutions is simulated using metadynamics. The local structure of 3BrY molecules in the clusters is then compared with the low‐temperature crystal structure of 3BrY, as well as with an alternative 3BrY high‐pressure crystal packing obtained through Parrinello–Rahaman molecular dynamics simulations. It is found that the interactions between the aromatic cores of 3BrY represent the main supramolecular motif observed in both the local structure of the prenucleation clusters and in the crystalline state. Within the clusters, these interactions lead to the presence of dimers and trimers locally arranged in crystal‐like configurations.